2017
DOI: 10.1155/2017/9478048
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Immunosuppressive and Th2 Immune Polarizing Effects of Antidiabetic Momordica charantia Fruit Juice

Abstract: The mechanism of action of the antidiabetic capacity of Momordica charantia is still under investigation. Here, we assessed phytochemical compositions, antioxidant activity, and effects of total and filtered fruit and leafy stem juices of Momordica charantia on human T cell proliferation and differentiation through quantification of Th1/Th2 cytokines. In the absence of stimulation, total fruit and leafy stem juices induced significant T cell proliferation. Under PHA stimulation, both juices potentiated plant-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…M. charantia fruit juice was prepared as we have previously described [ 2 ]. Briefly, 100 g of fresh fruits were manually ground and pressed with 100 ml of sterilized distilled water to obtain fruit juice according to slightly modified methods of Raza et al [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…M. charantia fruit juice was prepared as we have previously described [ 2 ]. Briefly, 100 g of fresh fruits were manually ground and pressed with 100 ml of sterilized distilled water to obtain fruit juice according to slightly modified methods of Raza et al [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
“…For our contribution, we have previously undertaken studies and demonstrated the antihyperglycemic effects of three African medicinal plants in diabetic pregnancy in rats [ 1 ]. Very recently, we have also shown the immune-modulatory effect of Momordica (M.) charantia [ 2 ], a plant commonly used in Africa and south Asia for diabetes treatment. During several decades, M. charantia is one of the plants which have gained most attention from several researchers [ 2 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The immunostimulatory effects of other Momordica species have been coincidentally described by a number of in vitro and in vivo studies. Leafy stem juices of M. charantia induced significant T cell proliferation and enhanced IFN-γ production (Fachinan et al, 2017). Augmented cell-mediated and antibody-mediated immunity evident by increased Delayed Type Hypersensitivity (DTH) and Haemagglutinating Antibody Titre (HAT), respectively, was observed after oral administration of Momordica charantia to immunized rats (Prasad et al, 2010).…”
Section: Day7 Day14mentioning
confidence: 99%